Comparative Analysis of IPv4 and IPv6 OpenVPN Protocol Performance Based on QoS Parameters (Journal of Advances in Information Systems and Technology, 2021)
Network security is still a big concern in data exchange because it involves users' data privacy. There are several ways to secure data exchange on the internet. One of them uses a Virtual Private Network (VPN), which functions as a tunnel in the public internet that securely connects users to the local network. This research will analyze the performance of the OpenVPN IPv4 and IPv6 protocols. The method used to determine the performance results is based on the QoS parameters. The performance analysis results obtained are throughput OpenVPN IPv6 is better, namely 198.155 Kbps on ICMP data packets, 35.704 Kbps on FTP data packets, and 17.698 on TCP data packets. The delay value of OpenVPN in IPv4 is superior, namely 1.4s for ICMP data packets, and on IPv6, FTP data packages are superior with 0.1s. Jitter values indicate OpenVPN IPv6 is better with similar results. Packet loss values on OpenVPN for both IPv4 and IPv6 protocols are 0%. Based on these results, throughput IPv6 OpenVPN on ICMP data packets and delay on FTP data packets is better than IPv4 OpenVPN.